2016
DOI: 10.1073/pnas.1607897113
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanics/molecular mechanics simulation of the ligand vibrations of the water-oxidizing Mn 4 CaO 5 cluster in photosystem II

Abstract: During photosynthesis, the light-driven oxidation of water performed by photosystem II (PSII) provides electrons necessary to fix CO 2 , in turn supporting life on Earth by liberating molecular oxygen. Recent high-resolution X-ray images of PSII show that the wateroxidizing center (WOC) is composed of an Mn 4 CaO 5 cluster with six carboxylate, one imidazole, and four water ligands. FTIR difference spectroscopy has shown significant structural changes of the WOC during the S-state cycle of water oxidation, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 57 publications
11
79
1
Order By: Relevance
“…In particular, we selected two different mutants, one reported as non-influencing mutant (E189Q; Strickler et al 2006) and another as high-influencing mutant (D61A; Debus 2014), regarding the intensities of the differential IR spectra (see Table 2). As comparison and control, we present the double differential spectra of the isotope labeled 13 C-1 A344 (WT* in Table 2, see Figs 5 and 6 for spectra), similarly as what previously reported by another work (Nakamura and Noguchi 2016). In the latter case, as expected, the effect of the isotopic exchange is localized in a relatively small spectral window, modifying mainly the neighborhood of the A344.…”
Section: Psii Modelssupporting
confidence: 71%
See 2 more Smart Citations
“…In particular, we selected two different mutants, one reported as non-influencing mutant (E189Q; Strickler et al 2006) and another as high-influencing mutant (D61A; Debus 2014), regarding the intensities of the differential IR spectra (see Table 2). As comparison and control, we present the double differential spectra of the isotope labeled 13 C-1 A344 (WT* in Table 2, see Figs 5 and 6 for spectra), similarly as what previously reported by another work (Nakamura and Noguchi 2016). In the latter case, as expected, the effect of the isotopic exchange is localized in a relatively small spectral window, modifying mainly the neighborhood of the A344.…”
Section: Psii Modelssupporting
confidence: 71%
“…To show the weaknesses and the critical points of the direct calculation of difference spectra, in the present work, we investigated several models of the natural Mn 4 Ca cluster present in PSII. As first, similar to what reported in a recent work (Nakamura and Noguchi ), we considered two different protonation patterns, in which the W2 molecule coordinating the Mn4 ion is present either as hydroxide or water molecule. In agreement with the previous study, we found a dramatic effect of the specific protonation of the W1 and W2 molecules, namely, PP1 (W1 = H 2 O, W2 = OH) and PP2 (W1 = H 2 O, W2 = H 2 O), on the calculated differential spectra (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Characteristic bands at 1450 -1350 cm Ϫ1 are due to the symmetric COO Ϫ stretching vibrations (78, 80 -85), whereas the coupled asymmetric COO Ϫ stretching bands appear at 1600 -1500 cm Ϫ1 , overlapping the amide II bands (NH bending and CN stretching vibrations of backbone amides) (78,82). The changes of these COO Ϫ bands during the S-state cycle are attributed to the structural changes of carboxylate residues around the Mn 4 CaO 5 cluster (80,81,(83)(84)(85). The obtained spectra showed characteristic features depending on the flash number, especially in the symmetric COO Ϫ region around 1400 cm Ϫ1 , reflecting high efficiencies of the S-state transitions.…”
Section: Flash-induced Ftir Difference Spectra Of S-state Transitionsmentioning
confidence: 99%
“…The Ca ion and four Mn ions are connected by five oxo-bridges, and Ca and Mn4 bind two terminal water ligands each (W1-W4; W2 may be a hydroxo ligand). [27][28][29][30] The remaining coordination sites of the Mn 4 Ca cluster are completed by bridging carboxy ligands supplied by the D1 and CP43 proteins of PSII (not shown). The only exception is the Mn1 site, which features one histidine ligand and is five-coordinate.…”
Section: Introductionmentioning
confidence: 99%